Ensino primário tipicamente rural no Estado de São Paulo: um estudo sobre as Granjas Escolares, os Grupos Escolares Rurais e as Escolas Típicas Rurais (1933-1968) - Moraes, Agnes Iara Domingos [UNESP] (2014)
In this work it is presented the research results of master's degree in education, with the overall objective of restoring aspects of the history of rural elementary school in the State of São Paulo, focusing the Granjas Escolares, Grupos Escolares Rurais and Escolas Típicas Rurais, implemented over the period from 1933 to 1968. Through historical approach, focused on bibliographic and documentary research, using as documentary corpus two educational journals – Journal of Education from 1933 to 1961 and the journal of Professor from 1934 to 1965; the annuaries of teaching in the State of São Paulo from 1935 to 1936 and from 1936 to 1937; the annual reports of the Regional Departments of education from 1933 to 1945; the messages of the Governors of the State of São Paulo; Federal legislation over 1933 and 1967; State legislation that regulated the rural education over 1933 and 1968 and theme-related books produced and in circulation in the period defined for the research. The results indicate that the studied schools were projected to meet the pressing demands on the historical moment of its implementation. These demands were related to the formation of a national identity, attachment of the man in the field, the sanitation diffusion, training for work, among others. The three types of schools studied represented a very restricted number of rural elementary schools in the State of São Paulo in Brazil and they presented many points converged with ruralist conception of education.